Theory of discrete fractional Sturm-Liouville equations and visual results - Bas, Erdal; Ozarslan, Ramazan (Amer Inst Mathematical Sciences-Aims, 2019)
In this article, we study discrete fractional Sturm-Liouville (DFSL) operators within Riemann-Liouville and Grunwald-Letnikov fractional operators with both delta and nabla operators. Self-adjointness of the DFSL operator is analyzed and fundamental spectral properties are proved. Besides, we get sum representation of solutions for DFSL problem by means of Laplace transform for nabla fractional difference equations and find the analytical solutions of the problem. Moreover, the results for DFSL problem, discrete Sturm-Liouville (DSL) problem with the second order, and fractional Sturm-Liouville (FSL) problem are compared with the second order classical Sturm-Liouville (CSL) problem. We display the results comparatively by tables and figures.
Keywords: fractional difference equations; Laplace transform; fractional differential equations; Sturm-Liouville; eigenfunctions, eigenvalues